Traditional Birth Attendant reorientation and Motherpacks incentive's effect on health facility delivery uptake in Narok County, Kenya: An impact analysis - John Emmanuel Kitui; Vaughan Dutton; Dirk Bester; Rachel Ndirangu; Susan Wangai; Stephen Ngugi (BMC, 2017)
Abstract Background A community health programme in Narok County in Kenya aimed to improve skilled birth assistance during childbirth through two demand side interventions. First, traditional birth attendants (TBAs) were co-opted into using their influence to promote use of skilled birth attendants (SBAs) at health facilities during delivery, and to accompany pregnant women to health facilities in return for a Ksh500 (Approximately USD5 as of August 2016) cash incentive for each pregnant mother they accompanied. Secondly, a free Motherpack consisting of a range of baby care items was given to each mother after delivering at a health facility. This paper estimates the impact of these two interventions on trends of facility deliveries over a 36-month period here. Methods Dependency or inferred causality was estimated between reorientation of TBAs and provision of Motherpacks with changes in facility delivery numbers. The outcome variable consists of monthly facility delivery data from 28 health facilities starting from January 2013 to December 2015 obtained from the District Health Information Systems 2 (DHIS2). Data were collected on the 13th, 14th or 15th of each month, resulting in a total of 35 collections, over 35 months. The intervention data consisted of the starting month for each of the two interventions at each of the 28 facilities. A negative binomial generalized linear model framework is applied to model the relationship as all variables were measured as count data and were overdispersed. All analyses were conducted using R software. Findings During the 35 months considered, a total of 9095 health facility deliveries took place, a total of 408 TBAs were reached, and 2181 Motherpacks were distributed. The reorientation of TBAs was significant (p = 0.009), as was the provision of Motherpacks (p = .0001). The number of months that passed since the start of the intervention was also found to be significant (p = 0.033). The introduction of Motherpacks had the greatest effect on the outcome (0.2), followed by TBA intervention (0.15). Months since study start had a much lower effect (0.05). Conclusion Collaborating with TBAs and offering basic commodities important to mothers and babies (Motherpacks) immediately after delivery at health facilities, can improve the uptake of health facility delivery services in poor rural communities that maintain a strong bias for TBA assisted home delivery.